Penyelesaian Perkara Kecelakaan Lalu Lintas Dengan Pelaku Anak, yang Mengakibatkan Korban Meninggal Dunia di Wilayah Polres Bantul - Boedi Hariyanto; Sigit Herman Binaji; Sigit Setyadi (Kajian Hasil Penelitian Hukum, 2019)
This study aims to study and analyze the settlement of traffic accident cases with child offenders, which resulted in fatalities in the Bantul Police Station and its constraints and efforts to resolve the obstacles. The results showed that the settlement of a traffic accident case with a child offender, which resulted in the death of a victim in the Bantul District Police area, began with a mere case and then involved children, so that the police  investigator conducted an investigation and case crime scene. If the BAP results contain evidence that points to the child as a suspect, Bapas conducts Litmas to the suspect, so a recommendation from Bapas for Diversi is published. Obstacles faced by Bantul Police investigators in the settlement of traffic accident cases with child offenders, which resulted in fatalities in the Bantul Polres area, including obstacles originating from children , constraints originating from law enforcement, and constraints originating from from the community. Then how to overcome these obstacles include improving the quality and quantity of human resources in Bantul Regional Police.